Penatalaksanaan Secara Konstruktif Dengan Crossword Puzzle Pasien Risiko Perilaku Kekerasan di RSJD dr. Arif Zainudin Surakarta - Deden Dermawan - Poltekkes Bhakti Mulia (Indonesian Journal on Medical Science, 2020)
Abstract: The risk of violent behavior is a condition in which a person takes action that can physically harm himself, others, and the environment. Symptoms of the risk of violent behavior are red face, tension, bulging eyes, clenched fists, clenched jaw, stiff body posture, loud talk, cursing with dirty words, throwing objects / other people attacking others and injuring themselves / people. The purpose of this study was to determine the crossword puzzle filling nursing management in controlling violent behavior in patients at risk of violent behavior. A qualitative descriptive research design with a nursing process approach. Population is patients at risk of violent behavior. The sampling technique was non-probability sampling with a purposive sampling approach with 4 research subjects with inclusion criteria of patients with a risk of violent behavior, and cooperative. The research instrument used interview guides, observation sheets, recorders, books and stationery. The analysis technique used interview transcripts and source triangulations. Data collection techniques by means of interviews, observation, and documentation study. The development of the 4 subjects after filling in the crosword puzzle for 2 weeks were as follows: 4 subjects wanted to fill in the easy question model and after being given the difficult question model the patient did not want to fill in and vent their emotions. Crossword puzzle is not effective for the risk of violent behavior.Keywords: crossword puzzle, risk of violent behaviorÂ Abstrak: Resiko perilaku kekerasan adalah suatu keadaan dimana seseorang melakukan tindakan yang dapat membahayakan secara fisik baik terhadap diri sendiri, orang lain, maupun lingkungan. Tanda gejala dari risiko perilaku kekerasan adalah muka merah, tegang, mata melotot, tangan mengepal, rahang mengatup, postur tubuh kaku, bicara keras, mengumpat dengan kata-kata kotor, melempar benda/orang lain menyerang orang lain melukai diri sendiri/orang. Tujuan dari penelitian ini adalah Untuk mengetahui penatalaksanaan keperawatan pengisian crossword puzzle dalam mengendalikan perilaku kekerasan pada pasien resiko perilaku kekrasan. Desain penelitian deskriptif kualitatif dengan pendekatan proses keperawatan. Populasi adalah pasien resiko perilaku kekerasan. Teknik pengambilan sampel non probalility sampling pendekatan purposive sampling dengan 4 subjek penelitian dengan kriteria inklusi pasien dengan resiko perillaku kekerasan, dan kooperatif. Instrumen penelitian menggunakan pedoman wawancara, lembar observasi, perekam, buku dan alat tulis. Teknik Analisa menggunakan transkrip wawancara dan Trianggulasi Sumber. Teknik pengumpulan data dengan cara wawancara, observasi, dan studi dokumentasi. Perkembangan 4 subjek setelah dilakukan pengisian crosword puzzle selama 2 minggu sebagai berikut:Â  4 subjek mau mengisi model soal mudah serta setelah diberikan model soal sulit pasien tidak mau mengisi serta meluapkan emosinya. Crossword puzzle tidak efektif untuk risiko perilaku kekerasan.Kata kunci: crossword puzzle, risiko perilaku kekerasan